Product-Based Learning Model through the Alignment of Mechanical Engineering Competencies with Industry - Heri Yudiono; Sonika Maulana; M. Burhan Rubai Wijaya; Rahmat Aprianto; Karsan Karsan (Faculty of Engineering, Universitas Negeri Yogyakarta, 2021)
The alignment of the competencies in the industry with vocational school is crucial to develop the graduate skills to comply with industry needs. Competency alignment can be performed through an innovative learning model by integrating the industrial activities into learning activities. This study assessed the feasibility of the product–based learning model to improve the mechanical engineering competence by aligning competencies of the vocational school with industry. This study used experimental research with one group pretest-posttest design. The study employed data analysis consisting of the T-test and the feasibility testing of the model. The effectiveness testing of the model was performed by comparing student’s achievement before and after using the learning model. The feasibility test was conducted on 39 students participating in the subject of Machining Process II. The results of the study revealed that there were significant differences in mechanical engineering competencies before and after using the learning model. These results indicated that the industry and stakeholders need to be involved in each stage of learning.